Acute effect of high-intensity aerobic exercise performed on treadmill and cycle ergometer on strength performance - Panissa, V. L. G.; Tricoli, V. A. A.; Julio, U. F.; Ribeiro, N.; de Azevedo Neto, R. M.; Carmo, E. C.; Franchini, E. (The Journal of Strength and Conditioning Research, 2015)
Concurrent training (i.e., combination of endurance with strength training) may result in negative interference on strength performance. Moreover, there are indications that the magnitude of this interference is dependent on endurance exercise mode. Thus, this study aimed to verify the acute effects of previous running and cycling on strength endurance performance. After the determination of the maximum intensity reached (Imax) during treadmill running and cycle ergometer pedaling and half-squat maximum strength (1 repetition maximum [1RM]), 10 physically active men were submitted to 3 experimental conditions: control condition (S) comprised of 4 sets of maximum repetitions at 80% 1RM, intermittent running (RS), and cycling (CS) conditions (15 × 1 minute:1 minute in the Imax) followed by the strength exercise (S). Maximum number of repetitions (MNR), total session volume (TV), and vastus lateralis electromyographic signal (VLRMS) were analyzed. It was observed that MNR and TV performed in set 1 in the S condition was superior to that performed in set 1 in the RS (p < 0.001) and CS (p < 0.001) conditions; and set 2 in the S condition was superior to set 2 only in the CS for the MNR (p = 0.032) and TV (p = 0.012). For the VLRMS, there was a main effect for repetition, with higher values in the last repetition compared with the second one (p < 0.01). In conclusion, an aerobic exercise bout before strength exercise impairs the subsequent strength endurance performance. In addition, the magnitude of the interference effect was higher after the aerobic cycling exercise.